Analisis Kinerja dan Kemampuan Daerah dalam Pelaksanaan Otonomi Daerah Kota Pontianak - Widyaningsih, Atria Tiffany (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
Discussion about the Regional Financial Performance and Capabilities required to be processed more deeply, then becomes a problem in this research are: the financial capacity of the region in the implementation of regional autonomy, especially in 2011-2014, when viewed from the degree of decentralization Fiscal Indicators (DDF), Degree of Fiscal Autonomy (DOF), Fiscal Capacity, Needs Fiscal Effort / Effectiveness Ratio Fiscal Position original revenue (PAD) and Tax Performance Indicators and Local Retribution in Pontianak. And will be discussed also about the level of local financial independence in 2011-2014 to support the organizers of regional autonomy as measured by the ratio of Regional Financial Independence and Relationship Patterns in Pontianak. Research conducted at the Office of Pontianak City BPKAD, with the quantitative descriptive analysis method which uses data measured in a numerical scale / number. (Kuncoro, 2003) This analysis aims to determine the level of local financial capacity, level of independence and the readiness of the local government of the city of Pontianak in the implementation of regional autonomy. Results from this study and the performance of Financial Ability in one regional assessed from the ratio of local independence that describes to the extent of financial dependence of local governments to the central government, obtained by comparing the acceptance of PAD to acceptance Assistance and Contribution Regions. From the year 2011-2014, the average calculation independence ratio Pontianak City generate value 21.22% Because of the value is between 0-25%, the city of Pontianak is considered to have very low financial capacity and have a pattern instructive relations with the central government, which where financial dependence on the central government is still low compared to the regional independence.